Interactive Teaching and Student Engagement: a case study at Preah Sihamoniraja Buddhist University (PSBU) - Baraing Roth (Journal of General Education and Humanities, 2026)
This study investigates the impact of interactive teaching methods on student engagement in English classes at Preah Sihamoniraja Buddhist University (PSBU) in Phnom Penh, Cambodia. This research aims to investigate how the use of more student-centred and interactive teaching methods can encourage students to become more involved and active in class, even when the class is perceived as boring, as traditional lecture-centred methods often are. The study used a quantitative method and collected data through structured questionnaires. Likert-scale questions were used to assess their thoughts and level of involvement in class; 63 students responded. Using the mean score and standard deviation, it was found which part of this interaction had the greatest effect on student involvement. The data clearly showed that this interactive teaching method enhances both student engagement and enthusiasm for learning new subject matter. The number of students who engaged in critical thinking was still insufficient in this experiment, a finding that suggests a need for more exercises that require them to solve problems or think more critically, though interactive teaching is effective.